On the geometry of algebraic curves having many real components - Huisman, J. (Revista Matemática Complutense, 2001)
We show that there is a large class of nonspecial effective divisors of relatively small degree on real algebraic curves having many real components i.e. on M-curves. We apply to 1. complete linear systems onM-curves containing divisors with entirely real support, and 2. morphisms of M-curves into P1.